Assessing the Cost Efficiency of Commercial Banks in Nepal: An Empirical Analysis - Gajurel, Dinesh (Journal of Comparative International Management, 2023)
This paper examines the cost efficiency and its determinants for Nepalese commercial banks by using semi-parametric methodology. We first estimate the efficiency and growth of productivity using Data Envelopment Analysis and then identify firm-specific attributes that potentially explain cost efficiencies. The first-stage results indicate a considerable level of cost inefficiency, which is largely caused by technical inefficiency. Additionally, there exists a low level of external (particularly regulatory) influence on the input mix, as indicated by a very low level of allocative inefficiency. The growth in productivity is low and even negative, mostly resulting from a lack of technological progress. The second-stage results indicate that state-owned banks are less cost-efficient than private banks (domestic and foreign), and size has a consistently inverse impact on cost efficiency. Banks with higher financial capital, larger loan ratios, and higher profits tend to be more cost efficient; however, banks with higher credit risk tend to be less cost efficient. Our findings have implications for policymakers, regulators, and bank managers as a better understanding of the level and sources of bank efficiency helps reduce inefficiencies, formulate regulations to enhance the overall efficiency of the banking system, and develop policies to promote competition and financial stability.